Zimbabwe National Family Planning Council (ZNFPC) client management system - Mugwenhi, Tafirei Samson (Midlands State University, 2018)
The chief purpose for this research was inclined towards solving the challenges that were being faced with regards to manual client tracking and updating at the Zimbabwe National Family Planning Council (ZNFPC). The new ZNFPC Client Management System is a web based system that utilizes internet facilities to deliver on the routine recording, tracking and updating service records and statistics at the organization. At the organization comes new and old clients for different family planning (FP) methods / services as well as other sexual reproductive health (SRH) services. Within the heath fraternity, it is of paramount importance to take and/or keep an accurate track of all clients’ medical history and health services history, and ZNFPC as a wing under the ministry of health (MoH) is not excluded. Facts pertaining to the settings and way of doing things that were prevailing in the council were gathered through the use of several fact finding methods that included interviews, questionnaires and observations amongst others. Discoveries through these fact finding methods laid the basis for the development of the new system that would solve the major problems of the old system. It was gathered without doubt from the clients that they solely desire that the council implement an efficient way of updating its clients on individuals’ next check-up or service dates as well as other general updates. This move would greatly reduce missed check-up / review dates and ultimately reduce unintended defaults and unplanned families. The system would be mainly used by the service providers in the council to capture clients’ personal details, medical history and services rendered on any particular day. Clients on the other side would receive updates via emails and SMSs. Service statistics generated by the system are also an important Management Information Systems tool that would aid managers and directorate in decision making. This documentation gives a detailed description of the functionality of the ZNFPC Client Management System.